Investigation of Fresh and Hardened Properties of Self-compacting Concrete Using Calcite and Fly Ash as Supplementary Cementitious Materials - Swapneel Satone; Dhananjay Parbat; Valsson Varghese; Avinash M Badar; Dipali P. Jasudkar; Manmohandas Goel (Engineering Research: Perspectives on Recent Advances Vol. 2, 2025)
Concrete is the second most widely consumed building material in the world because of its beauty, strength and durability. In an era of increased attention to the environmental impact of construction, engineered concrete performs well when compared to other building materials. This study evaluates the use of green materials such as fly ash and calcite as Supplementary Cementitious Materials (SCMs) in the manufacturing of Self Compacting Concrete (SCC). The main objective of this study is to show the number of ways in which the concrete industry can increase its compliance with the demands of sustainable development. Most recent research on SCMs has focused on a few areas: exploring new materials, increasing replacement amounts, developing better test methods, treating or modifying materials, and using additives to improve performance. An experimental investigation was conducted to assess the feasibility of using a combination of fly ash and calcite as SCMs in self-compacting concrete, and to evaluate their effect on workability and hardening properties. The study concluded that the elimination of vibrating equipment improves environment protection near construction and precast sites where concrete is being placed, reducing the exposure of workers to noise and vibration. In SCC, there is no chance of honeycomb, hence it gives a superior surface finish.